Influence of the exposure degree on the degradation of facades of buildings in Brasília - Brazil - Souza, Ana Luiza Rocha de (2024)
Facades play an important role in building performance and durability since these systems, one of the most external elements, are highly exposed to climatic degradation agents. The degradation process evolves over time, causing anomalies and performance failures, ultimately reducing the building’s service life. When directly influenced by the agents and mechanisms, the expected degradation of the systems that constitute the facade depends on the degree of exposure to the agents and how the degradation mechanisms act under different conditions. Given the relevance of the topic and the need for information on the degradation process of facade elements, this investigation aims to evaluate the relationship between the degradation measured in buildings in Brasília and the exposure degree of the facades, focusing on climatic degradation agents. The facades are evaluated regarding exposure to driving rain and solar radiation and classified into two groups: high exposure and low exposure. The sample degradation was quantified using the Degradation Measurement Method (DMM) and the General Degradation Factor (FGD). This methodology showed both the behavior models for the different exposure groups and allowed us to calculate estimated service life (ESL) values of approximately 26 and 35 years for facades with high and low exposures, respectively. The FGD values are higher for facades with high exposure compared to those with lower exposure. Additionally, North-oriented facades are the most critical, exhibiting the highest degradation levels due to the greater intensity of driving rain and incident solar radiation.